2015
DOI: 10.5021/ad.2015.27.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Results from the Patch Test to Para-Phenylenediamine in the TRUE Test in Patients with a Hair Dye Contact Allergy

Abstract: BackgroundPara-phenylenediamine (PPD) is the primary patch test screening agent for hair dye contact allergy (HDCA). However, no recent studies have been published that describe the results of reactions to patch tests using PPD and hair dyes in Korea.ObjectiveTo analyze the results of the patch tests to PPD using the thin-layer rapid use epicutaneous (TRUE) Test system in patients with HDCA and to investigate patients' awareness that hair dyes contains allergens, which cause the development of HDCA.MethodsEigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
5
10
0
Order By: Relevance
“…Thus, differences regarding the reactivation threshold may also have impacted the individual onset of the (cross‐) elicitation responses observed in two individuals with symptoms occurring within 15 min or as late as 1 week after the hair colour treatment (Table ). This is in line with the recently described variability of time intervals between hair dyeing and dermatitis onset (1 day up to 1 month) …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, differences regarding the reactivation threshold may also have impacted the individual onset of the (cross‐) elicitation responses observed in two individuals with symptoms occurring within 15 min or as late as 1 week after the hair colour treatment (Table ). This is in line with the recently described variability of time intervals between hair dyeing and dermatitis onset (1 day up to 1 month) …”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the recently described variability of time intervals between hair dyeing and dermatitis onset (1 day up to 1 month). 19 Ho et al 20 analysed the tolerance of PPD-containing hair dye products in PPD-allergic individuals based on the strength of their previous response to PPD under diagnostic patch testing: tolerance was recorded in 73% of 55 cases with a mild strength (+) and 49% of 61 patients with a moderate strength (++), but in none of 14 with a severe strength (+++). In contrast, we found tolerance to ME-PPDcontaining hair colorants in five cases with a strong diagnostic patch test reaction to PPD (+++), for three of them with a frequency of full hair colour treatments of every 4-7 weeks for dark to medium-dark and medium-light shades ( Table 4).…”
Section: Individual Idmentioning
confidence: 99%
“…From these results, it may appear that positive reactions to 1.0% o-aminophenol might have included false-positive reactions, and that a 1.0% concentration of this reagent may have been too high for patch testing. Lee et al reported that only 40% of patients with hair dye-related contact dermatitis showed positive reaction to PPD, and they concluded that, for diagnosing hair dye-related contact allergy, hair dye compounds other than PPD should be included (21). From the results of this study, we would be able to diagnose most patients by using PPD; however, testing only with PPD is insufficient to actually find all patients, because contact allergy to p-methylaminophenol, o-aminophenol and m-phenylenediamine will often be missed.…”
Section: Discussionmentioning
confidence: 99%
“…PPD is one of the most powerful skin allergic sensitizers, with topical application of 10% PPD shown to cause contact allergy in 100% of subjects within 5 applications [5] . Similarly, about 40% of hair dye allergy has been linked to PPD sensitivity [6] . Positive skin patch test to PPD can remain positive for over a month, which is unusual and another indicator of the intense sensitization [7] .…”
Section: Skin Reactions To Ppdmentioning
confidence: 99%